145 Pre-motor phase in autopsy-confirmed multiple system atrophy. Issue 12 (14th November 2019) - Vichayanrat, Ekawat; Pablo-Fernandez, Eduardo De; Valerio, Fernanda; Mathias, Christopher; Panicker, Jalesh; Holton, Janice; Warner, Thomas; Quinn, Niall; Iodice, Valeria
Abstract : Background: Non-motor features can be presenting symptoms and often precede the motor features in patients with multiple system atrophy (MSA). However there have been no studies specifically looking at the conversion time, clinical features and survival rate in autopsy-confirmed MSA patients. Methods: Medical records of 47 autopsy-confirmed MSA cases at the Queen Square Brain Bank who underwent clinical examination and cardiovascular autonomic testing at the National Hospital for Neurology were reviewed. Results: 15/47 (32%, M:F/9:6) MSA patients had non-motor autonomic features as an initial presentation before developing motor symptoms. Mean pre-motor phase duration was 3 (range 1–6) years. Among these 15 patients, the most common pre-motor features (87%) were genitourinary (erectile dysfunction in 7, bladder dysfunction in 6 patients); pre-motor symptomatic orthostatic hypotension (OH) and REM sleep behavioural disorder (RBD) occurred in one patient each. 5/15 patients developed cardiovascular autonomic failure and were initially diagnosed with pure autonomic failure (PAF). There was no difference in age of onset between patients presenting with motor and pre-motor autonomic features (p=0.67) or between different pre-motor presenting features and disease duration (p>0.05). Conclusions: Pre-motor autonomic features, including genitourinary, cardiovascular autonomic failure and RBD, are common presenting symptoms in MSA, accounting for almost one-third of patients. These features can predate motor symptoms by up to 6 years, or longer.